Menginvestigasi Produktivitas Marketing Era 4.0 Pada Bank Mandiri Berbasis Jalur Pelanggan (Studi Pada KCP Semarang Sisingamangaraja) - Widowati, Rahmani Tri Retno; Perdhana, Mirwan Surya (Master of Management Diponegoro University, 2020)
The purpose of this study is to determine the response of customers and the general public regarding customer lines (5A), determine the level of marketing productivity in the 4.0 era from the aspects of Purchase Action Ratio (PAR) and Brand Advocacy Ratio (BAR). The study was conducted with a sample / informant group of customers with a purposive sampling method of 30 people, and community group respondents with an accidental sampling method as many as 96 people. Customer path is measured from Aware, Appeal, Ask, Act, Advocade (5A) with mixed method analysis techniques. Research results: aware information sources, relationship and family recommendations, and personal experience. Regarding appeal, I really like the first time I found out / was offered a product. Demand ask, the informant is very confident of the products and actions taken to contact the service center. Actions, having high confidence then immediately decide to become a customer, the services he feels are also very satisfied. Demand advocate, proving that the informants are customers have very high loyalty, so they are willing to recommend to other parties. Marketing has a very high sales productivity, it can be seen from the PAR value of 0.98. A BAR of 0.99 indicates high sales growth, and at the same time proves that the marketing strategy is effective because there is very high customer loyalty.